Effect of dietary supplementation of Andrographis paniculata on milk yield and composition in Saanen and Jamnapari does - Hamzah, Siti Fatimah; Alimon, Abdul Razak; Yaakub, Halimatun; Jusoh, Shokri; Samsudin, Anjas Asmara @ Ab Hadi; Willoughby, R. V. (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
Supplementation of herbal containing high level of polyphenols in dairy goat diets is able to improve milk yield and composition and has been associated with antioxidant properties of the herbal plant supplementation. The objective of this study is to evaluate the effect of dietary supplementation of Andrographis paniculata (1.5%) on milk yield and milk composition in Saanen and Jamnapari lactating does in small dairy farm that belong to Mr. Rafik that located in Batang Benar Negeri Sembilan. Thirty two multiparous lactating does (16 Saanen and 16 Jamnapari) were used in this project. The does from each breed were divided into two groups and fed diets supplemented with or without Andrographis paniculata for a period of 3 month for both breed. There are effect of dietary treatment on dry matter intake and crude protein intakes (g/day) over the experimental period. However, there was no significant differences in digestibility for all nutrients measured. However, supplementation of A. paniculata to the diet showed significant increases on FCM milk yield for both morning and evening milking, and total milk yield, antioxidant and calcium contents compared to control diet. As far as the breed effect is concerned, milk from Jamnapari does had significantly higher contents of antioxidant and calcium in but there was a decrease in total milk yield. It was concluded that, A. paniculata group have higher milk yield and milk antioxidant content compared control group. This founding able increases the profit and adds value to the milk.